Electromagnetic Fields Modify Redox Balance in the Rat Gastrointestinal Tract - Sieroń, Karolina; Knapik, Katarzyna; Onik, Grzegorz; Romuk, Ewa; Birkner, Ewa; Kwiatek, Sebastian; Sieroń, Aleksander (Frontiers in Public Health, 2021)
Objective The aim of the study was to assess the influence of electromagnetic fields with divergent physical properties on the pro-oxidative and anti-oxidative balance in homogenates of the tongue, salivary glands, esophagus, stomach and small and large intestines of rats. Material and Methods Forty rats were randomly divided into four equal groups: a control group, a group exposed to low-frequency electromagnetic fields (LF-EMF; frequency: 50 Hz; intensity: 10 kV/m; magnetic induction: 4.3 pT), a group exposed to radio frequency electromagnetic fields emitted by mobile phones (RF-EMF; frequency: 900 MHz), and a group exposed simultaneously to LF-EMF and RF-EMF. After 28 consecutive days of the experiment, the following pro- and anti-oxidative markers were assessed in the gastrointestinal tract homogenates: superoxide dismutase (SOD) and its two isoenzymes (Mn-SOD, Cu,Zn-SOD) catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), glutathione S-transferase (GST) and total antioxidative capacity (TAC), total oxidative status (TOS) and malondialdehyde (MDA). Results In rats exposed to LF-EMF, higher concentrations of MDA or TOS were observed in the salivary glands, esophagus and small intestine homogenates in comparison to the control group. Additionally, in the group of rats opposite to the control, antioxidant activity was observed. The main differences included a higher activity of Cu,Zn-SOD in homogenates of the tongue, salivary glands and esophagus as well as decreased activity of CAT in homogenates of the tongue, esophagus and small intestine. In animals exposed to RF-EMF the concentration of TOS was higher in the large intestine than in control rats. The main difference of antioxidant activity was presented by decreased Cu,Zn-SOD in homogenates of the salivary glands, stomach, small and large intestine as well as CAT in homogenates of the tongue, esophagus, stomach and small and large intestine. Moreover, in rats exposed simultaneously to LF-EMF and RF-EMF, a lower concentration of TOS was observed. Antioxidant activity was presented by a decreased activity of CAT in homogenates of the tongue, esophagus, stomach and small and large intestine in comparison to the control group. Conclusion Among those applied in the study, LF-EMF caused the most significant disturbances of oxidative stress in the rat gastrointestinal tract.